Hmong, history of a people - Quincy, Keith (Eastern Washington University, 1995)
There are slightly more than six million Hmong worldwide, and close to a million in America. Yet few Americans know much about them. Originally non-Asians, they migrated to Siberia and then into China. For most of their history the Hmong have been perpetual migrants. In China, it was the only way they could avoid forced assimilation. Later, in Vietnam, Laos, and Thailand they again voted with their feet, drifting up into the mountains beyond the reach of state officials who abused them with impunity. After the Second World War, the Hmong of northern Vietnam and Laos allied themselves with the French, and later with the U.S., to fight against the Vietnamese communists. Nearly a third of the Laotian Hmong perished in combat or died from starvation and disease caused by the war. After the communist takeover, thousands more died in concentration camps, perished in rebellions, or were killed trying to escape to Thailand. Of those who did escape, nearly a hundred thousand resettled in the U.S.